Population biology of shrimp Macrobrachium jelskii (Miers, 1778) (Decapoda, Palaemonoidea) at the Grande River at northwest of the state of Minas Gerais, Brazil - Barros-Alves,Samara de Paiva (2012)
AIM: The population biology of the freshwater shrimp Macrobrachium jelskii was investigated here emphasizing the length-frequency distribution, sex ratio, reproductive period and juvenile recruitment. In addition, the abundance of individuals was correlated with the abiotic factors. METHODS: Samples were collected on a monthly basis from July 2005 to June 2007 along the river margin in shallow water of Grande River, at Planura region, State of Minas Gerais, Brazil (20º 09' S and 48º 40' W), using a trawl net (1.0 mm mesh size, and 2.0 m × 0.5 m wide). The fishing gear was handled by two people along the marginal vegetation of the Grande River in a course of 100 m, covered for one hour. In the laboratory, the specimens were identified, measured and sexed. RESULTS: A total of 2,789 specimens was analyzed, which corresponded to 1,126 males (549 juveniles and 577 adults) and 1,663 females (1,093 juveniles, 423 adults non-ovigerous and 147 ovigerous). The sex ratio differed significantly in favor of the females of M. jelskii (1:1.48; χ² = 103.95; p < 0.0001). The mean size of carapace length (CL) of females (6.32 ± 1.84 mm CL) was statistically higher than of males (5.50 ± 1.07 mm CL) (p < 0.001). The length-frequency distribution of the specimens revealed an unimodal pattern and non-normal distribution for males and females (W = 0.945; p < 0.01). No significant relationship between the abundance of M. jelskii and the environmental variables was observed (p = 0.799). CONCLUSION: The presence of ovigerous females and juveniles in the population suggests a continuous reproduction pattern and recruitment for M. jelskii at Planura region.